Development and validation of teaching profession problems scale. (2016)
This study has to do with development and validation of instrument to measure problems confronting the teaching profession. This study employed descriptive research design of survey type which does not involve manipulation of variables. The study made use of two hundred and forty teachers randomly selected from public primary and secondary schools in four local government areas in Ibadan land. The instrument consists of two sections, the first section was made up of demographic variables of the participants while the second section unis made up of 86 items related to leaching profession problems on a four-point likert scale of Strongly Disagree = 1, Disagree - 2, Agree = 3 and Strongly Agree = 4. Principal component analysis mid confirmatory factor analysis supported five factors of the Teaching Profession Problems Scale (TPPS). In selecting the items for the final scale, items with total-item correlation of less than 0.3, those with factor loadings of less than 0.4 and factor loadings of 0.4 on two or more factors were removed. The findings from this study showed that psychometric properties for Teaching Profession Problems Scale (TPPS) are reliable and valid measure for problems confronting the teaching profession in Nigeria. The findings demonstrated that the subscales of TPPS are internally consistent, well inter-correlated, and have a good construct validity. Also, the study reveal that TPPS has five factors which include Organizational issues, Government (or stakeholders) issues, Societal issues, Teacher- related issues and Professional body issues. Therefore, Teachers Registration Council of Nigeria (TRCN) and Nigeria Union of Teachers should intensify efforts for teaching to be fully professionalized. Teachers' salaries should be made attractive for them to be able to meet their basic needs while the payment of their salaries and allowances should not be delayed. Government should intensify efforts to renovate dilapidated school buildings and provide teaching-learning facilities. Continuing professional development and retraining of teachers should be taken more seriously by government and other stakeholders in education in order to enhance their professional knowledge and skills. Finally, teachers should change their attitude towards the profession and should not view teaching as inferior to other professions.